2018
DOI: 10.1208/s12248-018-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Combining Extracellular miRNA Determination with Microfluidic 3D Cell Cultures for the Assessment of Nephrotoxicity: a Proof of Concept Study

Abstract: Abstract.Drug-induced kidney injury is often observed in the clinics and can lead to longterm organ failure. In this work, we evaluated a novel in vitro system that aims at detecting whether compounds can cause renal proximal tubule damage in man. For this, we implemented organotypic cultures of human conditionally immortalized proximal tubule epithelial cells overexpressing the organic anion transporter 1 (ciPTEC-OAT1) in a threechannel OrganoPlate under microfluidic conditions. Cells were exposed to four kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Both types of experiments show clear transporter functionality, whereas the latter is the most complex functional assay. We have not assessed organic anion transporter (OAT) expression by the RPTEC used in this study, but 2D evaluation by Suter-Dick et al (36) showed no response to tenofovir, indicating absence of the OAT1 transporter. This limits the use of the cell line for assessment of transport of organic ions.…”
Section: Discussion and Outlookmentioning
confidence: 93%
“…Both types of experiments show clear transporter functionality, whereas the latter is the most complex functional assay. We have not assessed organic anion transporter (OAT) expression by the RPTEC used in this study, but 2D evaluation by Suter-Dick et al (36) showed no response to tenofovir, indicating absence of the OAT1 transporter. This limits the use of the cell line for assessment of transport of organic ions.…”
Section: Discussion and Outlookmentioning
confidence: 93%
“…Epithelial polarization has been confirmed in these chip systems by tight junction formation and the presence of primary cilia (Jang et al, 2013;Jansen et al, 2015;Weber et al, 2016;Vedula et al, 2017;Vormann et al, 2018;Vriend et al, 2018), as well as proof-of-concept studies indicating that transepithelial transport of anionic and cationic organic compounds is feasible (Weber et al, 2016;Jansen et al, 2019;van der Made et al, 2019;Stahl et al, 2020). Kidney-on-a-chip models have been used to study drug-induced toxicity (Jang et al, 2013;Sakolish et al, 2018;Suter-Dick et al, 2018;Weber et al, 2018;Vormann et al, 2018;Maass et al, 2019), but crucially have not previously been applied to study the implications of epithelial polarization and localization of drug transporters for replication of membrane-dependent drug toxicity in vitro.…”
Section: Introductionmentioning
confidence: 91%
“…After incubation, 100 μL of each sample, in three replicates each, was transferred to a 96‐well plate. The absorbance of the metabolized WST‐8 was measured using a multilabel plate reader (PHOMO, Photometer, Autobio, China) …”
Section: Methodsmentioning
confidence: 99%